Recriminalisation of smuggling in the system of combating economic crimes: analysis of criminal law - Колодін, Денис Олексійович; Колодін, Д. О.; Kolodin, Denys O.; Степаненко, Оксана Василівна; Степаненко, О. В.; Stepanenko, Oksana V.; Бубен, Каріна Вікторівна; Бубен, К. В.; Buben, Karina V. (Riga : Baltija Publishing, 2025)
The practice of smuggling, as a manifestation of the shadow economy, has historically been regarded as a significant threat to national security. This is due to the fact that it has the capacity to undermine fiscal stability, legitimate competition, and institutional trust. Recent amendments to Ukrainian criminal legislation, which have resulted in the reclassification of commodity smuggling as a criminal offence, underscore the necessity for a methodical and scientific examination of the subject under investigation. Studying the issue of the recriminalisation of smuggling is important for improving criminal legislation and for developing effective state policies in the field of economic security. This study aims to provide a comprehensive analysis of the criminal law aspects of the recriminalisation of smuggling as part of the system for combating economic crime. This analysis will take into account modern challenges, changes in Ukrainian legislation and international experience. The objective of the study is to ascertain the most effective methods of regulatory enhancement, harmonisation of administrative and criminal liability, and the assurance of effective law enforcement in the field of combating smuggling in the context of European integration. The research methodology consists of such methods as: formal-legal, comparative-legal, policy analysis method, empirical method and synthesis method. The article provides a criminal law analysis of the phenomenon of the recriminalisation of smuggling within the modern Ukrainian system for combatting economic crime. It considers the reasons, consequences and merits of reintroducing criminal liability for certain smuggling activities, particularly those involving goods not subject to excise duty or prohibited items. The national legal framework is analysed, as are the positions of domestic and international experts, and the comparative legal experience of other countries. A meticulous examination is conducted to ascertain the prospective hazards and favourable elements of this methodology with respect to safeguarding the economic stability of the state. The text goes on to outline interdisciplinary approaches to the problem, and determine which approaches are relevant for the formation of a balanced and effective system for combating economic crime.
Kolodin D. Recriminalisation of smuggling in the system of combating economic crimes: analysis of criminal law / D. Kolodin, O. Stepanenko, K. Buben // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. – 11(3). - P. 60-67. URL: https://doi.org/10.30525/2256-0742/2025-11-3-60-67
Keywords: recriminalisation of smuggling; economic crime; criminal law policy; customs law; cross-border crime; administrative liability; international co-operation